1998
DOI: 10.1038/sj.bmt.1701202
|View full text |Cite
|
Sign up to set email alerts
|

VIP (etoposide, ifosfamide and cisplatinum) as a salvage intensification program in relapsed or refractory Hodgkin’s disease

Abstract: Summary:Forty-two patients with refractory (15 patients) or relapsed (27 patients) Hodgkin's disease (HD) were included in a prospective single center study evaluating the efficacy of a regimen VIP combining etoposide 75 mg/m 2 /day days 1-5, ifosfamide 1.2 g/m 2 /day days 1-5 and cisplatinum 20 mg/m 2 /day days 1-5, one course every 4 weeks as salvage therapy in patients with refractory or relapsed Hodgkin's disease, potentially eligible for high-dose chemotherapy with reinjection of hematopoietic stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Although multiagent regimens like mini‐BEAM can produce high response rates and formed the induction chemotherapy and standard dose arms of the randomized trials reported by Linch et al4 and Schmitz et al,5 these and other regimens have significant shortcomings. Those shortcomings include myelosuppression with occasional fatal infection during neutropenia, requirement for hospitalization for drug administration, impairment of PBSC collection, and risk of secondary or late myeloid leukemia 6, 7, 9, 10, 12, 38, 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiagent regimens like mini‐BEAM can produce high response rates and formed the induction chemotherapy and standard dose arms of the randomized trials reported by Linch et al4 and Schmitz et al,5 these and other regimens have significant shortcomings. Those shortcomings include myelosuppression with occasional fatal infection during neutropenia, requirement for hospitalization for drug administration, impairment of PBSC collection, and risk of secondary or late myeloid leukemia 6, 7, 9, 10, 12, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…There are many salvage regimens that have been reported for recurrent or refractory Hodgkin lymphoma,6–12 and several are platinum‐based 9–12. An ideal salvage regimen should produce a high response rate with acceptable hematologic and nonhematologic toxicity, and it should not impair the ability to mobilize peripheral blood stem cells (PBSCs) for autologous transplantation.…”
mentioning
confidence: 99%
“…Although there was no difference in OS, FFTF was significantly improved in the ASCT group (55% versus 34%, P = .02). 22 Although there have been many published phase II studies reporting results of salvage regimens for relapsed or refractory Hodgkin lymphoma, [23][24][25][26][27][28][29][30][31][32][33] there are no RCTs and no consensus on the most effective second-line chemotherapy regimen. If the ultimate goal of salvage chemotherapy is to enable patients to proceed to ASCT, an ideal salvage regimen should produce a high response rate with acceptable hematologic and non-hematologic toxicity, and not impair the ability to mobilize peripheral blood stem cells for autotransplant.…”
Section: Salvage Chemotherapy and Autologous Transplantationmentioning
confidence: 99%
“…Many regimens have been reported, often containing a platinum-based agent, but no single regimen has emerged as the accepted standard. Table 2 provides a summary of commonly used salvage regimens [3,[13][14][15][16][17][18]. All of these have inferior or comparable response rates to those reported here and where data is given the haematological toxicity is generally comparable or higher.…”
Section: Discussionmentioning
confidence: 93%